2015
DOI: 10.5114/pwki.2015.49180
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet resistance and the role of associated variables in stable patients treated with stenting

Abstract: IntroductionNowadays, clopidogrel and acetylsalicylic acid (ASA) have become routinely applied therapies in percutaneous coronary interventions (PCI) with stenting.AimNumerous variables can interfere with antiplatelet responsiveness, so we aimed to investigate the role of different variables associated with ASA or clopidogrel resistance in stable coronary artery disease.Material and methodsA total of 207 patients undergoing elective PCI were included in the analysis. All patients received a loading dose of clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
2
10
0
3
Order By: Relevance
“…A similar effect was seen for the ward where patients were admitted, with Cardiology patients being significantly more prone to be responders than those in Neurology. The results of this study regarding the association between LDL levels and aspirin response were comparable with the results of previous studies [13][14][15][16].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A similar effect was seen for the ward where patients were admitted, with Cardiology patients being significantly more prone to be responders than those in Neurology. The results of this study regarding the association between LDL levels and aspirin response were comparable with the results of previous studies [13][14][15][16].…”
Section: Discussionsupporting
confidence: 94%
“…Beta-adrenergic receptor inhibitors (beta-blockers) have the opposite effect, increasing the chance of being a re- sponder by more than 4 times, these being in contrast with results reported by Uzun et al [13]. A similar effect was seen for the ward where patients were admitted, with Cardiology patients being significantly more prone to be responders than those in Neurology.…”
Section: Discussionmentioning
confidence: 64%
“…The study also showed that patients with higher ADP-induced platelet reactivity on clopidogrel also show diminished response to aspirin [comp. 26]. We have not, however, seen an increase in the risk of stent thrombosis in relation to arachidonic acid induced platelet reactivity alone.…”
Section: Discussionmentioning
confidence: 76%
“…Most studies examining platelet aggregation, either ADP or aspirin induced, were done in cohorts of stable coronary artery disease (CAD) patients after elective PCI procedures or in unselected all-comer populations [25, 26]. There are less studies in patients with ACS and the data on diabetic patients is mostly derived from subgroup analyses of large all-comer studies [27–30].…”
Section: Introductionmentioning
confidence: 99%
“…Наличие у пациентов хронической сердечной недостаточности (ХСН) со сниженной фракцией выброса ЛЖ, как с синусовым ритмом, так и с мерцательной аритмией, значительно повышает риск тромбоэмболических осложнений [1][2][3] из-за склонности к гиперкоагуляции и повышенному тромбообразованию. Резистентность к клопидогрелу значительно повышает риск повторного инфаркта миокарда (ИМ) и тромбоза стента [4][5][6][7], что, создавая «порочный круг», ведет к дальнейшему прогрессированию ХСН. Альтернативной является терапия новыми оральными антикоагулянтами [8][9][10][11][12], эффективность которых на примере истории болезни конкретного пациента будет рассмотрена ниже.…”
unclassified